Study of fluids flow in microchannels - Ng, Yuliang. (2009)
This project involves the study of two fluid flows in PDMS and PMMA microchannels. The objective is to control the laminar fluid diffusion interface (LFDI) by varying parameters such as flow rate ratio, viscosity and under the influence of electric field. Finding the appropriate light source to excite fluorescence flowing in PDMS microchannel is a prerequisite to solve all the problems in this project. A real time automatic controlling interface is crucial to control and indicate the interface location of the laminar fluid.